Comment on ‘‘Binding of alkaloid harmalol to DNA: Photophysical and calorimetric approach’’ - Alomar, María Lis (2014)
The present manuscript is a comment on the article entitled “Binding of alkaloid harmalol to DNA: Photophysical and calorimetric approach” by Sarita Sarkar and Kakali Bhadra (2014) [1]. In their article, the authors reported the chemical structure as well as the absorption spectra of harmalol at different pH. On the bases of the previous publications and our own present results, the assignment of the number of the acid-base species and the corresponding pKa values, as well as the chemical structure for each species are erroneous. These facts have strong effect on the conclusions reached by the authors, in terms of the interaction with DNA.